Metode Komunikasi Da’wah Ustadz Sirajuddin Rabbani Dalam Menda’wahkan Sunnah di Perumahan Bintang Metropol - Anshori, Muh. Nasution; Malik, Abdul (Jurnal Ilmiah Global Education, 2024)
This research aims to find out how Ustadz Sirajuddin Rabbani's da'wah communication method is in preaching the Sunnah at the Bintang Metropol Housing Complex. This type of research is field research, which is carried out directly by visiting respondents at home or other places to obtain data. or information. This research uses a qualitative approach which focuses on in-depth understanding of social phenomena. Data was collected through observation, interviews and documentation, each with different techniques. Data analysis was carried out descriptively, including reduction, presentation and drawing conclusions to describe phenomena systematically and find meaning in them. The research results show that in preaching the Sunnah at the Bintang Metropol Housing Complex, Ustadz Sirajuddin Rabbani applied three theoretical methods: Educational, Instructive, and Human Relations.